Implementasi Musyawarah Perencanaan Pembangunan (Musrenbang) Di Kelurahan Sei Mati Kecamatan Medan Maimun Kota Medan - Ichwanda, Rizki; Batubara, Beby Masitho; Sembiring, Walid Musthafa (Universitas Medan Area, 2024)
This article or writing aims to find out the implementation of Musrenbang in Sei Mati Village, Medan Maimun District, Medan City and what factors are obstacles to implementing Musrenbang in Sei Mati Village, Medan Maimun District, Medan City. The research method used is descriptive with a qualitative approach. Through observation, interviews and documentation. The theory used according to George Edward III is communication, resources, disposition/attitude of implementers, bureaucratic structure. The results of the research show that communication in the implementation of Musrenbang in Sei Mati Village, Medan Maimun District, Medan City is good. This is demonstrated in creating synergy and coordination of various elements. Human resources in the implementation of Musrenbang are not good, this is due to the emergence of community apathy towards participating in every stage of Musrenbang. The disposition or attitude of the implementers at the Musrenbang implementation stage is good. The bureaucratic structure in the implementation of Musrenbang in Sei Mati Village, Medan Maimun District, Medan City is good. Meanwhile, resource and communication constraints are factors that hinder the implementation of Musrenbang in Sei Mati Village, Medan Maimun District, Medan City. This is due to the community's lack of understanding and lack of outreach from the sub-district to the community.